Pengaruh Pemberdayaan Dan Keterlibatan Kerja Terhadap Kinerja Pegawai Negeri Sipil Pada Dinas Sosial Kabupaten Konawe - Fitria Fitria; Bindarto Bindarto (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aimed to determine and analyze the effect of empowerment and work involvement on the performance of civil servants at the Office of Forestry of Konawe regency, either simultaneously or partially. The study was explanatory in nature as it aimed to explain the position of variables under investigation as well as the relationship and effect of one variable on the others. Population and samples were 48 respondents which included all civil servants at the Office of Forestry of Konawe regency which were determined using a census method. Data were collected using a questionnaire that was administered to the respondents which were then analyzed using the multiple linear regression on the SPSS 20. Results of the study showed that: (1) empowerment and work involvement simultaneously had an effect on the performance of civil servants at the Office of Forestry of Konawe regency, (2) empowerment had a positively significant effect on the performance of civil servants at the Office of Forestry of Konawe regency, (3) work empowerment had a positively and not significant effect on the performance of civil servants at the Office of Forestry of Konawe regency.